A model-driven approach for mobile business information systems applications - Silva, L. (2022)
Context: Mobile BIS apps demand is increasing, with shorter time-to-market requirements, but their production faces problems, such as handling business rules concurrently, multiple platforms, localization and extensibility. Objective: Propose a generative approach for mobile BIS apps that will mitigate the identified problems. Method: We adopted the Design Science Research methodology, that helps gaining problem understanding, identifying systemically appropriate solutions, and in evaluating innovative solutions. Results: We identified the problem and its motivation, defined the objectives for a solution, designed and developed a prototype generative tool for BIS apps, demonstrated its usage and evaluated how well it mitigates a subset of the identified problems in an observational study. Limitations: Several issues are pending such as distributed business rules enforcement and the formalization of the required transformations from the PIM to several platform-specific models (PSMs). Conclusion: We intend to contribute for reducing BIS apps time-to-market, while improving the maintainability of those apps.